THE USE OF ANIMATION MOVIE IN TEACHING RECOUNT TEXT FOR STUDENTS’ PREWRITING ACTIVITY - Rusnah, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractMost of students’ problems in writing are that they do not know how to generate and develop the idea for their writing. To help the students to overcome their problems, the researcher used animation movie as media to teach students’ prewriting activity. To help them to use their own opinion of an idea in their writing, the researcher chooses recount text. This research was conducted in a pre-experimental one group pretest-posttest design and investigated whether the use of animation movie is effective in teaching writing recount text for students’ prewriting activity to the tenth grade students of Vocational School 2 Pontianak in academic year 2016/2017. The class which was taken by the researcher was class TOI (Teknik Otomasi Industri) which consists of 30 students. The technique of data collecting was measurement and the tool of data collecting was written test. Based on the result of the data computation, it was obtained that the t-test score (18.30) was higher than t-table (2.045) at α = 0.05. This prove that teaching recount text by using animation movie was significantly increased the students’ score in writing. Therefore, the null hypothesis is rejected while the alternative hypothesis is accepted and the effect of the treatment is categorized as strong effect. Keywords : Animation Movie, Recount Text, Prewriting  AbstrakSebagian besar masalah siswa dalam menulis adalah bahwa mereka tidak tahu bagaimana untuk menghasilkan dan mengembangkan ide untuk tulisan mereka. Untuk membantu siswa untuk mengatasi masalah mereka, peneliti menggunakan film animasi sebagai media untuk mengajarkan kegiatan prapenulisan siswa. Untuk membantu mereka dalam menggunakan pendapat mereka sendiri dari ide dalam tulisan mereka, peneliti memilih recount teks. Penelitian ini dilakukan dalam satu kelompok desain pretest-posttest pra-eksperimental dan menyelidiki apakah penggunaan film animasi efektif dalam mengajar menulis recount text untuk kegiatan prapenulisan siswa untuk siswa kelas X SMK 2 Pontianak pada tahun akademik 2016 / 2017. Kelas yang diambil oleh peneliti adalah kelas TOI (Teknik Otomasi Industri) yang terdiri dari 30 siswa. Teknik pengumpulan data adalah pengukuran dan alat pengumpulan data adalah tes tertulis. Berdasarkan hasil perhitungan data, diperoleh bahwa nilai t-test  (18.30) lebih tinggi dari t-tabel (2,045) pada α = 0,05. Ini membuktikan bahwa mengajarkan recount text dengan menggunakan film animasi meningkatkan secara signifikan nilai siswa dalam menulis. Oleh karena itu, hipotesis nol ditolak sedangkan hipotesis alternatif diterima dan efek dari perlakuan dikategorikan sebagai efek yang kuat. Kata kunci: Film Animasi, Teks Recount, Prapenulisan